Feeding whole-plant ensiled corn stover affects growth performance, blood parameters, and Cecal microbiota of Holdobagy goose - Wang, Xianze; Li, Guangquan; Wang, Huiying; Liu, Yi; Yang, Yunzhou; Wang, Cui; Gong, Shaoming; He, Daqian (Frontiers in Veterinary Science, 2023)
Introduction The aim of this study was to investigate the effects of adding whole-plant ensiled corn stalks (WECS) to the diet of Holdorbagy geese on their growth performance, serum parameters, and cecal microbiota. Geese farming is an important agricultural practice, and optimizing their diet can contribute to better growth and health outcomes. However, there is limited research on the utilization of WECS as a feed source for geese. Understanding the potential effects of WECS on growth, blood parameters, and cecal microbiota can provide valuable insights into its feasibility and impact on geese farming practices. Methods A total of 144 six-week-old Holdorbagy geese were randomly assigned to one of three groups: a control group (0% WECS), a group fed 15% WECS and 85% concentrated feed (15% WECS), and a group fed 30% WECS and 70% concentrated feed (30% WECS). The trial period lasted for three weeks, during which the growth performance, serum parameters, and cecal microbiota were assessed. Results The results revealed significant findings in different aspects. Firstly, the feed-to-gain ratio (F/G ratio) of the 15% WECS group was significantly higher than that of the control group (p<0.05), indicating potential challenges in feed efficiency. Additionally, the average daily feed intake (ADFI) of both the 15% and 30% WECS groups was significantly higher than that of the control group (p<0.05), suggesting increased appetite or palatability of the diet containing WECS. In terms of serum parameters, the level of lactate dehydrogenase (LDH) in the 30% WECS group was significantly lower than that in the control group (p<0.05). Moreover, there was a tendency for increasing Fe levels and decreasing Zn levels with higher levels of WECS supplementation, although the differences were not statistically significant (p<0.05). Furthermore, the principal coordinate analysis showed significant differences in the composition of cecal microbiota among the three groups (p < 0.01). The observed_species, Shannon, and Pielou_e indices of the 30% WECS group were significantly higher than those of the 0% and 15% WECS groups (p<0.05), while the Simpson index of the 15% WECS group was significantly lower than that of the control group (p<0.05). Discussion The results indicate that the addition of WECS to the geese diet has both positive and negative effects. The study suggests that WECS can be a long-term stable feed source for geese, which can contribute to reducing feeding costs. However, it is important to monitor the amount of WECS added as it can affect the absorption of Zn by geese. Supplementation of Zn in the diet might be necessary to meet the needs of geese. Notably, adding 30% WECS to the diet can increase the richness, evenness, and diversity of the cecal microbiota, indicating potential benefits to gut health. In conclusion, this study highlights the potential of WECS as a feed source for geese. It provides valuable insights into the effects of WECS on growth performance, serum parameters, and cecal microbiota. These findings contribute to optimizing geese farming practices, improving feed utilization, and enhancing overall productivity and well-being of geese. Further research is needed to determine the optimal inclusion level of WECS and to explore strategies for mitigating any negative effects.